2018
DOI: 10.3390/cancers10100347
|View full text |Cite
|
Sign up to set email alerts
|

NACC1, as a Target of MicroRNA-331-3p, Regulates Cell Proliferation in Urothelial Carcinoma Cells

Abstract: The nucleus accumbens-associated protein 1 (NACC1) is a transcription factor constitutively expressed in the urothelium, where it regulates cell growth, senescence, autophagy, and epithelial-mesenchymal transition. microRNA (miRNA) constitutes a class of small non-coding RNAs which are involved in cell proliferation, differentiation, and progression of tumors. miRNAs and their target molecules are utilized for molecular diagnosis of urothelial carcinoma. NACC1 is one of several putative target molecules of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(57 reference statements)
0
15
1
Order By: Relevance
“…Our previous study showed that miR‐331‐3p promotes proliferation and metastasis of hepatocellular carcinoma, and other researchers found similar effects of miR‐331‐3p in pancreatic cancer . However, other researchers discovered antitumor functions of miR‐331‐3p in urothelial cancer, gastric cancer, and cervical cancer . The functions of miR‐331‐3p in NSCLC were also ambiguous, and little was known about the targets and signaling pathways regulated by miR‐331‐3p in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that miR‐331‐3p promotes proliferation and metastasis of hepatocellular carcinoma, and other researchers found similar effects of miR‐331‐3p in pancreatic cancer . However, other researchers discovered antitumor functions of miR‐331‐3p in urothelial cancer, gastric cancer, and cervical cancer . The functions of miR‐331‐3p in NSCLC were also ambiguous, and little was known about the targets and signaling pathways regulated by miR‐331‐3p in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 13 ] confirmed that the miR-30a level is decreased in BLCA, and miR-30a hinders the progression of BLCA cells. Therefore, based on the regulatory effect of miRNA on the progression of BLCA, numerous miRNAs are promising molecular therapeutic targets of BLCA, such as miR-133b [ 14 ], miR-429 [ 15 ], and miR-331-3p [ 16 ]. However, it is still unknown whether miR-19a-3p is dysregulated in BLCA and whether it has the function of regulating the progression of BLCA.…”
Section: Introductionmentioning
confidence: 99%
“…As a transcriptional repressor, NAC1 regulates cell growth, senescence, epithelial–mesenchymal transition, and autophagy. NAC1 prevents cytotoxicity by stabilizing hypoxia-inducible factor-1α and regulating glucose levels, thereby playing a role in the hypoxic tumor environment ( 31 ). NAC1 forms a homodimer or heterodimers with other binding partners through the BTB/POZ domain and exerts transcriptional inhibition through the recruitment of histone deacetylase ( 32 ).…”
Section: Discussionmentioning
confidence: 99%